Perancangan Interior Pusat Tata Rias dan Rambut Rever Academy di Surabaya - Livia Faustyani Seloadji; Sriti Mayang Sari; M. Taufan Rizqy (Intra, 2015)
Rever Academy is one of the educational institutes that creates professionals in make up and hair-do in international quality. This institute is one of the well-known make up and hair styling training centers in Surabaya. This interior design of Rever Academy uses the site on one of the buildings in Surabaya named Spazio Office Tower. The location is in Western Surabaya, to be exact in the Jalan Lingkar Dalam. This design aims to create a facility of training center for make up and hair-do that can meet the needs of students and visitors with the smokeys concept that combines the color of black, white and brown to give a more interesting atmosphere (elegant) but still keep the characteristic of Rever itself. Therefore, it is hoped that the students and customers will feel more comfortable inside the salon area. Apart from that, this design aim to increase the previous income, create a qualified employee, and escalate the staff and employee performance.